A TEACHER’S AUTONOMY IN ASSESSING STUDENTS’ PERFORMANCE: A BRIEF CONCEPTUAL REVIEW ON THE ASSESSMENT OF LEARNING OUTCOMES - Abdu, Wamaungo Juma (EARR (Educational Administration Research and Review), 2019)
In formal schooling, testing/ or assessments are always done on entry, and on exit of the student. Assessment during entry is  carried out to assess the entry behaviour of a student, while the on-exit assessment is conducted to know how well students have achieved on the learning objectives. This means that assessment of a student has always had a strong foundation in the ‘hands of the teacher’.  Having taught, a teacher understands the students than any other assessor or evaluator. However, this is not the case in most countries, more so in the developing world, where students’ testing/assessment has always been done by the national examination bodies, a thing which terminates the teacher’s role in student’s assessment, hence hindering sincere evaluation of learners. Mr. Obama describes such a situation as teachers forced to spend their academic years preparing students to fill in bubbles on standardized tests (Cody, 2011). This Obama comment implies that teachers should be given authority in a substantive manner towards a more balanced method for evaluating students learning and achievement. In this paper therefore, I describe the need for a teacher’s autonomy in testing and or assessing students’ performance [school assessment] versus the national examinations organized by the national examination body under the ministry of education..